Pengaruh Dana Perimbangan Terhadap Kemandirian Keuangan Daerah Kabupaten Tolitoli - Maskur Maskur; Hariani Hanapi; Fatimah Fatimah (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to determine the effect of balancing funds on Regional Financial Independence in Tolitoli Regency. The variables studied are balancing funds (X) and regional financial independence (Y). The sampling technique in this study used a saturated sample technique. The research instrument used in this study was a ratio scale with a simple regression analysis technique where the data was analyzed using the SPSS for Windows 23 program. Simple linear results show that balancing funds have a positive and significant effect on regional financial independence in Tolitoli district.